2020
DOI: 10.1093/rheumatology/keaa543
|View full text |Cite
|
Sign up to set email alerts
|

Sex and gender differences in axial spondyloarthritis: myths and truths

Abstract: Mounting evidence reveals evident sex differences in physiology, disease presentation and response to medication in axial SpA (axSpA). Unfortunately these data are often neglected in clinical practice and research. In this review, myths that still exist on diagnosis, disease manifestation and drug effectiveness were argued against data of the most recent literature. The aim is to increase awareness of sex differences in the clinical aspects of axSpA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 86 publications
6
75
2
1
Order By: Relevance
“…Confirming this, Lee et al (2007) demonstrated a more severe radiographic damage among men who showed higher median BASRI−spine scores both in unadjusted and adjusted analyses for age and disease duration. On the other hand, the signs of peripheral involvements such as dactylitis, enthesitis, or swollen joint count appear to be significantly more prevalent in women ( Kennedy et al, 1993 ; Rusman et al, 2020 ). Extra-articular manifestations also appear with a higher rate in female patients ( Landi et al, 2016 ).…”
Section: Gender Differences In Clinical Phenotypes In Axial Spamentioning
confidence: 99%
“…Confirming this, Lee et al (2007) demonstrated a more severe radiographic damage among men who showed higher median BASRI−spine scores both in unadjusted and adjusted analyses for age and disease duration. On the other hand, the signs of peripheral involvements such as dactylitis, enthesitis, or swollen joint count appear to be significantly more prevalent in women ( Kennedy et al, 1993 ; Rusman et al, 2020 ). Extra-articular manifestations also appear with a higher rate in female patients ( Landi et al, 2016 ).…”
Section: Gender Differences In Clinical Phenotypes In Axial Spamentioning
confidence: 99%
“… 29 Most studies have revealed that men are more likely to show worse hip involvement and higher BASRI spine and modified Stoke Ankylosing Spondylitis Spine Score compared with women. 29 …”
Section: Discussionmentioning
confidence: 99%
“…The scoring of the radiographs considered erosions, joint space alterations, and sclerosis. Erosions were graded from 0 to 3 (grade 0, no erosions; grade 1, small, isolated erosions [1][2] or a questionable single erosion; grade 2, de nite erosions [3-5; <3 mm] or a larger single erosion [>3 mm]; and grade 3, multiple [>5] or con uent erosions). Each of the four segments was independently assessed for the slice with the maximum number of erosions in both the transverse and coronal views.…”
Section: Ct Scoring Systemmentioning
confidence: 99%
“…Ankylosing spondylitis (AS) is a chronic in ammatory arthritis affecting the sacroiliac joints (SIJs) and the spine, commonly occurring in childbearing age 1 . Although AS was previously believed to predominantly affect men, recent studies have shown that the incidence of AS in women is as high as one in every three women 2 . Pregnancy is a major issue faced by female AS patients of childbearing age.…”
Section: Introductionmentioning
confidence: 98%